Literatur Review Dampak Penyinaran Brakiterapi Terhadap Life Survival Pasien Kanker Serviks - Dwi Kumara Rai Akbar; Ni Putu Rita Jeniyanti; Daksa Ganapati (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Cervical brachytherapy is a type of treatment for cervical cancer by providing direct radiation to the cancer or tumor area. The brachytherapy itself is usually a booster combined with external radiotherapy. Evaluation of the success of radiation can be seen from the survival rate of patients or local control. In patients, survival and local control can be influenced by several prognostic factors such as the stage of the cancer, the size of the cancer diameter, and the pathology of the cancer itself. The aim of this research is to determine the impact of brachytherapy radiation on the life survival of cervical cancer patients by paying attention to the relationship between cancer stage, cancer size, cancer pathology on patient survival. This research uses a qualitative descriptive method with a literature study approach regarding the impact of brachytherapy radiation on patient life survival. cervical cancer. It was concluded that prognostic factors such as tumor or cancer size, cancer stage and cancer pathology in cervical cancer have a relationship with patient survival.